PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN (STUDI KASUS: CINEMA XXI IMAX GANDARIA CITY, JAKARTA) - SOLI NONI CECILIA SINAGA; MUCHSIN SAGGAF SHIHAB; KRISFARAH SYARFUAN (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The objective of this study is to examine the effect of experiential marketing on customer satisfaction, taking the case study of Cinema XXI IMAX Gandaria City, Jakarta. The concepts of experiential marketing (i.e. strategic experiential modules and experience providers) and customer satisfaction were taken from various resources. Both primary and secondary data were employed. Secondary data were taken from journals, books, and articles. Primary data were collected using self-administered questionnaire which were distributed to the respondents through online and offline method. Respondents were those who had watched at Cinema XXI IMAX Gandaria City, Jakarta for at least two times in the last six months. Using purposive sampling technique, a total sample of 100 respondents was obtained. Validity and reliability tests were employed to examine the research instruments. The statistical data were analyzed by SPSS software version 17.0. The multiple linier regression analysis was employed to verify the hypotheses. The result shows that strategic experiential modules and experience providers partially and simultaneously, had significant influence on customer satisfaction.